Effect of Land Preparation and Land Arragement on Soil Properties, Growth and Yield of Red Pepper (Capsicum annum) in Peat land - Maftuah, Eni; Hayati, Afiah (Jurnal Hortikultura Indonesia (JHI), 2019)
Peatlands are potential to be used as red pepper development areas. The technology of land preparation and land management is indispensable in the utilization of peatlands. The study aimed to study the effect of land preparation on soil fertility, growth and yield of red peppers. The research was carried out on peatland in Kalampangan village, Sebangau Sub-District, Kodya Palangkaraya, (-2 O179’9’’S, 144O1’31’’ E, 53,8m) from June to October, 2017. The experiment used Split Plot design, 3 replications. The main plot is types of land arrangement (U1 = without rise beds and U2 = with rise beds). The plot is a type of land preparation (A1=slash, burn, A2=slash, compost, A3=slash, mulch, A4= slash, compost, plastic mulch). Observations were made on plant growth, soil pH and P available on soil and red pepper yields. The highest yield of red pepper was reached on the treatment of land arrangement of beds system combined with land clearing system, then compostable materials+plastic mulch, while the lowest yield on the without bed + soil treatment on slash and weed was used for mulch. The result of pepper plant in peat soil is influenced by soil pH and P concentration is available in soil. Keywords: bed system, slash-burn, slash-compost, slash-mulch, plastic mulch